Coaggregates of Regulatory T Cells and Islet Cells Allow Long-term Graft Survival in Liver Without Immunosuppression. Issue 5 (May 2015) - Takemoto, Naohiro; Konagaya, Shuhei; Kuwabara, Rei; Iwata, Hiroo
Abstract : Background: Transplantation of islets of Langerhans (islets) has been investigated in the clinic to treat patients with insulin-dependent diabetes mellitus. Islet grafts have been maintained by administering immunosuppressive drugs, which can lead to complications in the long term. Alternatives to immunosuppressive therapy are eagerly desired. In this study, we examined the transplantation of coaggregates of CD4 + CD25 + regulatory T (Treg) cells. Methods: Coaggregates of Treg cells from C57BL/6 mice and islet cells from BALB/c mice were prepared on agarose hydrogel with small round-bottomed wells. Four hundred coaggregates were transplanted into the livers of streptozotocin-induced diabetic C57BL/6 mice without systemic immunosuppression. Results: The Treg cells and islet cells were distributed randomly in the coaggregates. When 400 coaggregates were transplanted into 9 C57BL/6 mice via the portal vein, 6 of the 9 recipients demonstrated blood glucose less than 250 mg/dL for more than 100 days. A number of insulin-positive cells were observed in the livers at 120 days after transplantation. Conclusions: The Treg cells and islet cells were distributed randomly in the coaggregates. After intraportal transplantation of the coaggregates, Treg cells in the aggregates enabled the long-term survival of allogeneic islet cell grafts in the liver without the use of immunosuppressive drugs. Abstract : Aggregates of islets and treg-enabled allogeneic islet survival long-term, thus raising the hopes of reduced immmunosuppressant requirements for islets. Supplemental digital content is available in the text.